Językowe sposoby autoprezentacji (na przykładzie) regionalnego ośrodka telewizyjnego w Archangielsku - Zagórska, Katarzyna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The article comprises an academic reflection on linguistic methods of self-presentation, used on regional television in Arkhangelsk. The material was collected in 2018 when the centre was celebrating its 55th anniversary. Moreover, earlier research in television broadcast in the north of Russia was taken into account. Editorial self-presentation is conducted in different ways. It embraces articles published on the website of the radio station and anniversary materials broadcasted on-air which later are uploaded on the web as podcasts. Self-presentation is also created by the image of the radio station reconstituted thanks to agenda, daily news feeds from 2018, examined in the context of sources from 2001-2018. Linguistic analysis is the affirmation of the medium’s form which is listener-oriented. What is more, within last few years the growth of axiological dimension was observed (for instance: religious magazines). Some website as well as on-air statements provide a persuasive step in order to create positive self-presentation. The radio station is seemed to be modern, professional and familiar with every human being, who is interested in social problems.